T Cell Immunosenescence after Early Life Adversity: Association with Cytomegalovirus Infection - Elwenspoek, Martha M. C.; Sias, Krystel; Hengesch, Xenia; Schaan, Violetta K.; Leenen, Fleur A. D.; Adams, Philipp; Mériaux, Sophie B.; Schmitz, Stephanie; Bonnemberger, Fanny; Ewen, Anouk; Schächinger, Hartmut; Vögele, Claus; et al. (Frontiers in Immunology, 2017)
Early life adversity (ELA) increases the risk for multiple age-related diseases, such as diabetes type 2 and cardiovascular disease. As prevalence is high, ELA poses a major and global public health problem. Immunosenescence, or aging of the immune system, has been proposed to underlie the association between ELA and long-term health consequences. However, it is unclear what drives ELA-associated immunosenescence and which cells are primarily affected. We investigated different biomarkers of immunosenescence in a healthy subset of the EpiPath cohort. Participants were either parent-reared (Ctrl, n=59) or had experienced separation from their parents in early childhood and were subsequently adopted (ELA, n=18). No difference was observed in telomere length or in methylation levels of age-related CpGs in whole blood, containing a heterogeneous mixture of immune cells. However, when specifically investigating T cells, we found a higher expression of senescence markers (CD57) in ELA. In addition, senescent T cells (CD57+) in ELA had an increased cytolytic potential compared to senescent cells in controls. With a mediation analysis we demonstrated that cytomegalovirus infection, which is an important driving force of immunosenescence, largely accounted for elevated CD57 expression observed in ELA. Leukocyte telomere length may obscure cell specific immunosenescence; here, we demonstrated that the use of cell surface markers of senescence can be more informative. Our data suggest that ELA may increase the risk of cytomegalovirus infection in early childhood, thereby mediating the effect of ELA on T cell specific immunosenescence. Thus, future studies should include cytomegalovirus as a confounder or selectively investigate cytomegalovirus seronegative cohorts.